2007
DOI: 10.1158/1078-0432.ccr-07-0465
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HER2 Low-Level Copy Gain in Barrett's Cancer: Implications for Fluorescence In situ Hybridization Testing in Tissues

Abstract: Purpose: HER2 may be a relevant biomarker in Barrett's cancer. We compared three HER2 laboratory methods, standard fluorescence in situ hybridization (FISH), image-based threedimensional FISH in thick (16 Am) sections, and immunohistochemistry, to predict patient outcome. Experimental Design: Tissue microarray sections from 124 Barrett's cancer patients were analyzed by standard FISH on thin (4 Am) sections and by image-based three-dimensional FISH on thick (16 Am) sections for HER2 and chromosome-17, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Nevertheless, the majority of cases were contained in both tissue microarrays so that correlation between immunohistochemistry, bright field double in situ hybridisation and fluorescence in situ hybridisation could be performed in approximately 100 cases. Discrepancies between the various in situ hybridisation methods and immunohistochemistry in our study may not only be caused by methodical or technical differences or the 'grey zone' of low-level gains 12 but also represent the phenomenon of intratumoral heterogeneity of ErbB2 expression in gastro-oesophageal adenocarcinomas, [23][24][25][26] because the cores of the donor blocks were obtained from slightly different tumour areas. Therefore, a heterogeneous distribution of ErbB2-positive cell clones may also be responsible for those divergent findings.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Nevertheless, the majority of cases were contained in both tissue microarrays so that correlation between immunohistochemistry, bright field double in situ hybridisation and fluorescence in situ hybridisation could be performed in approximately 100 cases. Discrepancies between the various in situ hybridisation methods and immunohistochemistry in our study may not only be caused by methodical or technical differences or the 'grey zone' of low-level gains 12 but also represent the phenomenon of intratumoral heterogeneity of ErbB2 expression in gastro-oesophageal adenocarcinomas, [23][24][25][26] because the cores of the donor blocks were obtained from slightly different tumour areas. Therefore, a heterogeneous distribution of ErbB2-positive cell clones may also be responsible for those divergent findings.…”
Section: Discussionmentioning
confidence: 79%
“…18,21,22 This phenomenon frequently occurs in oesophagogastric carcinomas 1,3,23 and can readily be recognised by this method. We have compared bright field double in situ hybridisation data with fluorescence in situ hybridisation data from a previously published study 12 and found a significant correlation between bright field double in situ hybridisation and both conventional fluorescence in situ hybridisation and the more complex but more sensitive 3D fluorescence in situ hybridisation. For breast cancer, similar observations were reported by others who described a high concordance in the assessment of ErbB2 amplification between fluorescence in situ hybridisation and the light-microscopy-based techniques of silver in situ hybridisation and bright field double in situ hybridisation, respectively, with advantages in terms of handling, orientation within the slides and in cases of intratumoral heterogeneity for bright field double in situ hybridisation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations